MicroRNAs: New Players in the Pathobiology of Preeclampsia - Bounds, Kelsey R.; Chiasson, Valorie L.; Pan, Lu J.; Gupta, Sudhiranjan; Chatterjee, Piyali (Frontiers in Cardiovascular Medicine, 2017)
Our understanding of how microRNAs (miRNAs) regulate gene networks and affect different molecular pathways leading to various human pathologies has significantly improved over the years. In contrary, the role of miRNAs in pregnancy-related hypertensive disorders such as preeclampsia (PE) is only beginning to emerge. Recent papers highlight that adverse pregnancy outcomes are associated with aberrant expression of several miRNAs. Presently, efforts are underway to determine the biologic function of these placental miRNAs which can shed light on their contribution to these pregnancy-related disease conditions. The discovery that miRNAs are stable in circulation coupled with the fact that the placenta is capable of releasing them to the circulation in exosomes generates a lot of enthusiasm to use them as biomarkers. In this review, we will summarize the recent findings of our understanding of miRNA regulation in relation to PE, a hypertensive disorder of pregnancy. Particular emphasis will be given to the role of key miRNA molecules such as miR-210 and miR-155 that are known to be consistently dysregulated in women with PE.